Pharmacological Evaluation of Antidepressant-Like Effect of Genistein and Its Combination with Amitriptyline: An Acute and Chronic Study - Gaurav Gupta; Tay Jia Jia; Lim Yee Woon; Dinesh Kumar Chellappan; Mayuren Candasamy; Kamal Dua (Advances in Pharmacological Sciences)
The present study was designed to evaluate the acute and chronic antidepressant effect of genistein in combination with amitriptyline in mice. Animals were divided into six groups (n=6) for treatment with water, genistein, or amitriptyline, either alone or in combination for ten days. Animals were subjected to locomotor activity testing; tail suspension test (TST); and forced swim test (FST) and immobility time was recorded on day one and day ten. Acute treatment of all treatment groups did not significantly reduce the immobility time (p>0.05). Chronic treatment of combination of genistein (10 mg/kg) and amitriptyline (5 mg/kg and 10 mg/kg) significantly reduced the immobility time as compared to control group (p<0.001) and was comparable to amitriptyline alone (10 mg/kg). However, no changes in anti-immobility activity in combination of subeffective doses of genistein (5 mg/kg) and amitriptyline (5 mg/kg) were observed. Genistein at its standard dose (10 mg/kg) rendered synergistic effects in combination with subeffective dose of amitriptyline (5 mg/kg) and additive effects in combination with therapeutic dose of amitriptyline (10 mg/kg).